Cardiac arrest as an age-dependent prognosticator for long-term mortality after acute myocardial infarction: the potential impact of infarction size. Issue 2 (1st March 2019) - Sulzgruber, Patrick; Schnaubelt, Sebastian; Koller, Lorenz; Goliasch, Georg; Niederdöckl, Jan; Simon, Alexander; El-Hamid, Feras; Rothgerber, David-Jonas; Wojta, Johann; Niessner, Alexander
Abstract: Background: The development of cardiac arrhythmias resulting in cardiac arrest represents a severe complication in patients with acute myocardial infarction. While the worsening of the prognosis in this vulnerable patient collective is well known, less attention has been paid to its age-specific relevance from a long-term perspective. Methods: Based on a clinical acute myocardial infarction registry we analysed 832 patients with acute myocardial infarction within the current analysis. Patients were stratified into equal groups ( n =208 per group) according to age in less than 45 years, 45–64 years, 65–84 years and 85 years and older via propensity score matching. Multivariate Cox regression analysis was used to assess the age-dependent influence of cardiac arrest on mortality. Results: The total number of cardiac arrests differed significantly between age groups, demonstrating the highest incidence in the youngest population with 18.8% ( n =39), and a significantly lower incidence by increasing age (−11.6%; P =0.01). After a mean follow-up time of 8 years, a total of 264 patients (31.7%) died due to cardiovascular causes. While cardiac arrest was a strong and independent predictor for mortality within the total study population with an adjusted hazard ratio of 3.21 (95% confidence interval 2.23–4.61; P <0.001), there was no significant association with mortality independently in very young patients (<45 years; adjusted hazard ratio of 1.73, 95% confidence interval 0.55–5.53; P =0.35). Conclusion: We found that arrhythmias resulting in cardiac arrest are more common in very young acute myocardial infarction patients (<45 years) compared to their older counterparts, and were able to demonstrate that the prognostic value of cardiac arrest on long-term mortality in patients with acute myocardial infarction is clearly age dependent.